Sosialisasi Manajemen Keuangan dan Akses Pembiayaan untuk Pelaku UMKM di Desa Sei Rampah, Kecamatan Sei Rampah - Suci Etri Jayanti S; Rapat Piter Sony Hutauruk; Rika Surianto Zalukhu; Fitrianingsih Fitrianingsih; Bobby Hartanto; Kumala Vera Dewi; Suwadi Suwadi; Cici Puspaningrum; Murbanto Sinaga; Sri Winda Hardiyanti Damanik; Bayu Arif Prabudi (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
The MSME actors in Sei Rampah Village lack adequate understanding of financial management principles. Moreover, they face challenges in accessing business financing sources. This prompted the service team to conduct a community service activity in the village. The activity was organized in the form of a socialization program aimed at improving business owners' understanding of managing business finances and strategies for accessing financing sources. The program was attended by 20 participants. The methods employed in this activity were lectures and interactive discussions. The stages of the community service included the preparation phase and the implementation phase. This activity had a positive impact on the MSME actors in the village. Their knowledge of financial management and access to financing sources increased. The MSME actors stated that they now understand how to manage business finances and strategies to access financing sources. This indicates that the community service activity carried out has made a positive contribution to business owners in Sei Rampah Village..